EFFECTIVENESS OF DIABETIC FOOT EXERCISES USING SPONGES AND NEWSPAPERS ON FOOT SENSITIVITY IN PATIENTS WITH DIABETES MELLITUS - CORRIGENDUM - Siti Fadlilah; Adi Sucipto; Nazwar Hamdani Rahil (Belitung Raya Foundation, Indonesia, 2020)
In the article by Fadlilah et al. (2019) published in the December 2019 issue of Belitung Nursing Journal, the following ORCID for Adi Sucipto was incorrectly inserted on page 237: “https://orcid.org/0000-0002-1693-4495” The authors retract this ORCID and change to https://orcid.org/0000-0001-6740-1835. They also apologize for the error. The corrected article can be seen in the following link: https://doi.org/10.33546/bnj.822